PsycEXTRA Dataset 2013
DOI: 10.1037/e546872013-340
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial function and sleep: Associations of flow-mediated dilation with perceived sleep quality and rapid eye movement (REM) sleep

Abstract: SummaryEndothelial function typically precedes clinical manifestations of cardiovascular disease and provides a potential mechanism for the associations observed between cardiovascular disease and sleep quality. This study examined how subjective and objective indicators of sleep quality relate to endothelial function, as measured by brachial artery flow-mediated dilation (FMD). In a clinical research center, 100 non-shift working adults (mean age: 36 years) completed FMD testing and the Pittsburgh Sleep Quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…However, in contrast to the prior findings correlating low sleep quality and CVD risk, the present study revealed that young individuals exhibiting low sleep quality reported no significant or clinically meaningful differences in vascular function when compared with individuals exhibiting high sleep quality. These findings contradict previous research using both subjective (Pittsburgh Sleep Quality Index or the Sleep-Wake Experience List) and objective (polysomnography) sleep quality assessments in which low sleep quality was associated with reduced upper limb vascular function (Behl et al, 2014;Bonsen et al, 2015;Cooper et al, 2014). A notable difference between the present study and the aforementioned studies is the average age of participants.…”
Section: Sleep Quality and Vascular Functioncontrasting
confidence: 99%
“…However, in contrast to the prior findings correlating low sleep quality and CVD risk, the present study revealed that young individuals exhibiting low sleep quality reported no significant or clinically meaningful differences in vascular function when compared with individuals exhibiting high sleep quality. These findings contradict previous research using both subjective (Pittsburgh Sleep Quality Index or the Sleep-Wake Experience List) and objective (polysomnography) sleep quality assessments in which low sleep quality was associated with reduced upper limb vascular function (Behl et al, 2014;Bonsen et al, 2015;Cooper et al, 2014). A notable difference between the present study and the aforementioned studies is the average age of participants.…”
Section: Sleep Quality and Vascular Functioncontrasting
confidence: 99%
“…Thus, long sleep duration may be related to poor sleep quality, and poor sleep quality was found to be associated with insulin resistance, 31 alteration of hypothalamic-pituitaryadrenal system activity, 32 increased sympathetic activity, 33 and endothelial function impairment. 34,35 This may partially explain the association between long sleep duration and increased arterial stiffness. Further research is needed to explore their mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] In addition, general population evidence supports associations between insomnia symptoms and biological mechanisms underlying CVD development, including systemic inflammation,31 altered coagulation,[32][33][34][35][36][37][38] and endothelial dysfunction. [55][56][57] There are study limitations that warrant consideration. First, our insomnia symptoms assessment was obtained only at baseline and relied on a single item.…”
mentioning
confidence: 99%